CO2 gasification of Powder River Basin coal catalyzed by a cost-effective and environmentally friendly iron catalyst. (1st May 2015) - Zhang, Fan; Xu, Deping; Wang, Yonggang; Argyle, Morris D.; Fan, Maohong
Graphical abstract: SEM images of the char sample and the corresponding distribution of iron atom clusters from EDS. Highlights: Iron catalyst was reduced to metallic iron in coal pyrolysis. SEM and EDS images shows the catalytic effect of iron on char gasification. The shrinking core model is more suitable than the random pore model for this work. The catalytic iron species were initially the metallic iron and FeO, and then changed to FeO and Fe3 O4 . Abstract: CO2 gasification of a sub-bituminous Wyodak coal from the Powder River Basin (PRB) was conducted in a fixed-bed laboratory gasifier at atmospheric pressure with FeCO3 as a catalyst precursor. The effect of iron on the coal pyrolysis was evaluated by thermo-gravimetric analysis (TGA). Scanning electron microscopy (SEM) was employed to characterize the iron performance in the char gasification. The iron species and oxidation states during the coal gasification, characterized by X-ray diffraction (XRD) and Mössbauer spectroscopy, indicate a complex interaction between the reaction atmosphere and temperature, but generally proceed through reduction to FeO and metallic iron during pyrolysis, followed by subsequent reoxidation to Fe3 O4 during gasification with CO2 . The catalytic effect of iron was also quantitatively evaluated by kinetic analysis using shrinking core and random pore models, with the shrinking core model providing superior results. Results show that the apparent activation energy was 92.7 kJ/mol for the untreated coal, which decreased to 58.3 kJ/mol for the coal with 3 wt% Fe. FeCO3 was shown to have a significant catalytic effect on the Wyodak coal gasification with CO2 .